2021
DOI: 10.3389/fmed.2021.673556
|View full text |Cite
|
Sign up to set email alerts
|

New Pandemic: Obesity and Associated Nephropathy

Abstract: Incidence of obesity related renal disorders have increased 10-folds in recent years. One of the consequences of obesity is an increased glomerular filtration rate (GFR) that leads to the enlargement of the renal glomerulus, i.e., glomerulomegaly. This heightened hyper-filtration in the setting of type 2 diabetes irreparably damages the kidney and leads to progression of end stage renal disease (ESRD). The patients suffering from type 2 diabetes have progressive proteinuria, and eventually one third of them de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 158 publications
(230 reference statements)
1
17
0
3
Order By: Relevance
“…Activation of the RAAS and enhanced sympathetic activity in obese patients lead to increased levels of aldosterone, which reflexively lead to increased renal tubular reabsorption of sodium salts, resulting in water and sodium retention (54). The activation of RAAS in obese patients leads to hemodynamic changes such as increased of GFR and renal plasma flow (RPF), which causes glomerular hyperfiltration, compensated glomerulomegaly, segmental sclerosis, and promoting the progression of MetSrelated renal damage (55)(56)(57). Hormone regulation disorder and ectopic lipid deposition in obese patients can directly or indirectly affect the structure and function of renal intrinsic cells (52).…”
Section: Obesitymentioning
confidence: 99%
“…Activation of the RAAS and enhanced sympathetic activity in obese patients lead to increased levels of aldosterone, which reflexively lead to increased renal tubular reabsorption of sodium salts, resulting in water and sodium retention (54). The activation of RAAS in obese patients leads to hemodynamic changes such as increased of GFR and renal plasma flow (RPF), which causes glomerular hyperfiltration, compensated glomerulomegaly, segmental sclerosis, and promoting the progression of MetSrelated renal damage (55)(56)(57). Hormone regulation disorder and ectopic lipid deposition in obese patients can directly or indirectly affect the structure and function of renal intrinsic cells (52).…”
Section: Obesitymentioning
confidence: 99%
“…Am häufigsten entstehen chronische Nierenerkrankungen infolge einer arteriellen Hypertonie, eines Diabetes mellitus oder einer Adipositas mit metabolischem Syndrom [ 16 , 17 ]. Eine frühzeitige und moderne Therapie ist gerade bei dieser Patient:innengruppe möglich und kann erfolgreich sein, das Stadium der terminalen Niereninsuffizienz zu vermeiden.…”
Section: Chronische Nierenerkrankungenunclassified
“…Serum concentrations of inflammatory markers are elevated in patients with CKD compared with those with normal kidney function, and they are associated with worsening kidney function in the general population [3,4]. Furthermore, many studies have demonstrated that body mass index (BMI, kg/m 2 ) is a potential predictor of proteinuria, glomerular filtration rate (eGFR) decline, and development of end-stage renal disease [5][6][7]. The increased risk for CKD among obese individuals, in addition to the underlying cardiometabolic abnormalities, can be due to excess adiposity-associated chronic inflammatory process, which contributes to early pathogenic mechanisms of kidney injury [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have demonstrated that body mass index (BMI, kg/m 2 ) is a potential predictor of proteinuria, glomerular filtration rate (eGFR) decline, and development of end-stage renal disease [5][6][7]. The increased risk for CKD among obese individuals, in addition to the underlying cardiometabolic abnormalities, can be due to excess adiposity-associated chronic inflammatory process, which contributes to early pathogenic mechanisms of kidney injury [7]. However, some studies reported negative roles of obesity for CKD on an inflammatory basis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%